Respon Ketahanan Beberapa Varietas Tahan Tungro terhadap Inokulum Kabupaten Pinrang - Rini Ismayanti; Ristanti Nuria Laili Isnaini; Firmansyah Firmansyah (Seminar Nasional Lahan Suboptimal, 2020)
Ismayanti R, Isnaini RLN, Firmansyah F.  2020.  Resistance of several tungro-resistant varieties to the inoculum of Pinrang. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The use of resistant varieties is currently reliable in efforts to prevent tungro disease, but the possibility of broken in resistance causes the need for monitoring or re-testing of resistant varieties that have been released with inoculation sources from endemic areas.This study aims to determine the durability of resistance of tungro resistant varieties to Pinrang inoculums. The study used isolate sources from Toe Village, with  the T1 - T4 and V1 - V4 class varieties, as a comparison  used Utri Merah and the TN1. The design used was a RAK with ten treatments and three replications. Inoculation was carried out for 24 hours by entering two green leafhoppers for one plant that had been aquisition for 48 hours. Observations were made up to three weeks after inoculation.  Tukad Unda had the smallest plant height reduction 4.2%, not much different from the Utri Merah resistant comparison of 4.64%, while IR20 had the highest plant height reduction  of 47.64%, exceeding the TN1 susceptibility comparison of 46.70%. The lowest disease index was found in the comparison variety Utri Merah (1.67) which was not significantly different from Tukad Petanu (2.67) and Tukad Unda (3.33). The highest disease index was IR20 (8) which was not significantly different from the TN1 susceptible comparison (6.5). IR64  with IP 5.67 were also not significantly different from TN1. Tukad Petanu have an IP of 2.67 which is classified as resistant, while the IR20 (T1) has an IP of 7.5 which is classified as susceptible.